Ag nanoprism metamaterial based tunable plasmonic logic gate - Yang, Hanning; Owiti, Edgar O.; Li, Siren; Pei, Yanbo; Shi, Hongyan; Sun, Xiudong (IOP Publishing, 2017)
A metamaterial comprised of asymmetrically arranged Ag nanoprisms has been proposed and investigated in this paper. The metamaterial shows a polarization dependent PIT effect. The metamaterial with its periodic length along a y-axis less than 400 nm shows two tunable transmission dips. When the periodicity is increased above 400 nm, the metamaterial shows three adjustable transmission dips against the polarization state. By choosing different wavelengths of incident light, the metamaterial can be used as plasmonic Boolean logic gates. The working wavelengths of these plasmonic devices can then be adjusted by controlling the fillet radius of Ag nanoprism in metamaterial. These results offer great potential in developing polarization dependent tunable plasmonic information processing devices.
Keywords: PIT effect; Metamateria; Boolean logic gate